Mechanical and Durability Properties of Cement-Stabilized Recycled Concrete Aggregate - Qingfu Li (Sustainability, 2020)
This research investigates the effect of using recycled concrete aggregate (RCA) as a partial replacement of natural aggregate (NA) on the mechanical and durability-related properties of a cement-stabilized recycled concrete aggregate (CSR) mixture. In this case, mixtures were prepared with 0%, 40%, 70%, and 100% (by weight) RCA to replace NA, and cement contents of 4%, 5%, and 6% were used in this study. Test parameters included the replacement ratio, cement content, and curing time. Tests were carried out to establish the unconfined compressive strength (UCS), indirect tensile strength (ITS), drying shrinkage, and water loss ratio of each mix proportion. The preliminary results of UCS and ITS tests indicated that the incorporation of RCA resulted in a decrease of strength compared with a cement-stabilized macadam (CSM) mixture, but the seven-day strength of the CSR mixture met the related requirements of road bases. The increase in cement content and curing time had an obvious effect on strength improvement. The drying shrinkage test showed that the drying shrinkage properties of the CSR mixture were obviously reduced with a high replacement ratio. It is evident that the CSM mixture presented a better drying shrinkage performance than that of the CSR mixture.